Randomized trial of bolus ephedrine or mephentermine for maintenance of arterial pressure and fetal outcome during spinal anesthesia for the cesarean section - Thomas S Linette; T Gurumurthy (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: Spinal anesthesia remains the preferred choice for cesarean deliveries, but hypotension is one of the common complications which may have detrimental effects on both the mother and fetus. In this study, we compared the efficacy and adverse effects of bolus doses of ephedrine hydrochloride and mephentermine sulfate administered intravenously to treat spinal-induced hypotension and the fetal outcomes through Apgar scores and umbilical cord blood gas analysis in the lower segment cesarean section. Material and Methods: In this prospective, randomized, double-blind study, 60 patients undergoing the lower segment cesarean section (LSCS) under spinal anesthesia were randomized into two groups of 30 each using computer-generated random numbers which were kept in an opaque envelope. Patients were pre-loaded with Ringer's lactate solution 10 ml/kg before the spinal anesthesia. Hypotension was defined as the fall in systolic blood pressure of less than or equal to 20% of the baseline or systolic blood pressure of less than 90 mmHg. Whenever hypotension occurred, patients in group E (ephedrine) received a bolus dose of ephedrine 6 mg intravenous and patients in group M (mephentermine) received a bolus dose of mephentermine 6 mg intravenous. Intra-operative recording included maternal hemodynamic parameters and the number of bolus doses of study drugs required to treat maternal hypotension and the adverse effects of study drugs. The Apgar score and umbilical cord blood gas values were recorded. Data were analyzed by analysis of variance test, Student's t-test, and Chi-square test. A P value of < 0.05 was considered as significant. Results: There was a statistically significant (p < 0.05) increase in systolic and mean arterial blood pressure at the second min and fourth min after administration of ephedrine in group E compared to mephentermine in group M. The systolic blood pressure at the second min in the ephedrine group was 114.3 ± 12.06, whereas in the mephentermine group, it was 106.10 ± 8.41 and was statistically significant (p < 0.05). At the fourth min, the systolic blood pressure in the ephedrine group was 115.03 ± 8.87, whereas in the mephentermine group, it was 108.46 ± 8.10 and was statistically significant (p < 0.05). There was a transient increase in heart rate immediately after administration of spinal anesthesia. The mean number of bolus doses of vasopressor consumption was 2.4 (14.4 mg) in the ephedrine group and 2 (12 mg) in the mephentermine group. The umbilical cord blood gas analysis and Apgar scores were similar in both the groups. Three patients (10%) developed bradycardia in the mephentermine group compared to the ephedrine group (0%). The incidence of nausea (13.3% vs 3.3%) and vomiting (10% vs 1%) was higher in the ephedrine group compared to the mephentermne group, and it was not statistically significant (p > 0.05). No significant differences were observed in the umbilical arterial blood pH and Apgar scores. Conclusion: In conclusion, after hypotension, ephedrine and mephentermine administration as bolus doses are equally efficacious in preventing spinal-induced hypotension in patients undergoing the cesarean section and are associated with similar neonatal outcomes.